PENINGKATAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SD N 2 PURBALINGGA WETAN PURBALINGGA - Anisatul Fitri; Okto Wijayanti (UM Purwokerto Press, 2026)
Grade IV students at SD N 2 Purbalingga Wetan face learning challenges particularly low levels of engagement in asking questions and responding during lessons. Some students choose to play with their friends during class, causing them to lose focus and not fully participate in learning activities. This study aims to analyze the improvement of student activeness and academic achievement in the subject of Pancasila Education. This Classroom Action Research (CAR) was carried out over two cycles. The subjects of the research were 23 fourth-grade students at SD Negeri 2 Purbalingga Wetan, located at JL Letnan Satu Jl. Lettu Kuseri, Purbalingga Wetan, Purbalingga, Central Java 53317. Each cycle consisted of four stages: (1) Action planning, (2) Action implementation, (3) Observation, and (4) Reflection. The results showed an increase in student activeness scores in each cycle. In the first cycle, the average score of student activeness was 2.53, categorized as